2020
DOI: 10.1111/acem.13987
|View full text |Cite
|
Sign up to set email alerts
|

Mobile Smartphone Technology Is Associated With Out‐of‐hospital Cardiac Arrest Survival Improvement: The First Year “Greater Paris Fire Brigade” Experience

Abstract: After reading the article, participants should be able to whether identification and activation of first responders using a mobile smartphone app can improve survival following outof-hospital cardiac arrest. Activity Disclosures This activity received no commercial support. CME Editor Corey Heitz discloses no relevant financial relationships. This activity underwent peer review in line with standards of editorial integrity and publication ethics. Conflicts of interest have been identified and resolved in accor… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
15
0
1

Year Published

2020
2020
2025
2025

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 18 publications
(16 citation statements)
references
References 28 publications
0
15
0
1
Order By: Relevance
“…A citizen responder programme in France, StayingAlive, was evaluated by Derkenne et al and found an association between activation of CPR trained volunteers and increased OHCA survival [25]. Originally, the programme included trained volunteers, but in 2019 the programme expanded to accept non-trained volunteers [25,26]. Volunteers not trained in CPR can be used as a resource for non-CPR tasks, for example bringing the nearest AED to the cardiac arrest location.…”
Section: Discussionmentioning
confidence: 99%
“…A citizen responder programme in France, StayingAlive, was evaluated by Derkenne et al and found an association between activation of CPR trained volunteers and increased OHCA survival [25]. Originally, the programme included trained volunteers, but in 2019 the programme expanded to accept non-trained volunteers [25,26]. Volunteers not trained in CPR can be used as a resource for non-CPR tasks, for example bringing the nearest AED to the cardiac arrest location.…”
Section: Discussionmentioning
confidence: 99%
“…Dispatching first responders to OHCA strengthens the chain of survival and increases the likelihood of good neurological outcome [ 18 , 19 , 36 ]. This study illustrates the impact of the pandemic on FR schemes and gives an overview over the corresponding measures taken to mitigate the risks for responders and patients.…”
Section: Discussionmentioning
confidence: 99%
“…However, these pilot programs have to be carefully evaluated because relevant factors for designing farreaching community CPR training programs are not well defined. In this context, smartphone applications might also be helpful in future CPR trainings [25][26][27][28].…”
Section: Discussionmentioning
confidence: 99%